Low cost methodology to determine the modulus of elasticity by static flection of beams of angelim pedra (Hymenolobium petraeum) (Research, Society and Development, 2022)
The aim of this paper is to determine the Modulus of Elasticity (MOE) by using the Principle of Virtual Work and deflection values obtained experimentally from a beam made of angelim pedra (Hymenolobium petraeum) timber, through a low-cost methodology. Three timber beams used to determine MOE were obtained in Açailândia – MA commerce, with cross-sections of (60,0 x 43,0) mm² and (55,0 x 40,0) mm² and equal lengths of 5500 mm. Three point timber beams with free span of 4500 mm were loaded with 20 kgf, 40 kgf and 60 kgf. MOE values varied between 13039,13 MPa and 13505,28 MPa, with mean value and coefficient of variation equal to 13225,01 MPa and 1,36%, respectively. To give a greater support to the comparative analysis, experimental MOEs were compared with literature review. Finally, the methodology applied on the timber of the species Hymenolobium petraeum, presented satisfactory results to the Modulus of Elasticity by static flection.